2005
DOI: 10.1007/s00066-005-1345-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Skin Measurements Correlate with EORTC/RTOG-Common Toxicity Criteria

Abstract: For classification of acute radiation toxicity there seems to be no need to replace the common CTC scoring by technical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…Momm et al reported that the skin color (especially red, the a* value) depended on the radiation dose applied to the skin and that the objective spectrophotometric measurements correlated well with the subjective CTC scores [14]. They concluded that for classification of acute radiation toxicity there seems to be no need to replace the common CTC scoring with technically more sophisticated methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Momm et al reported that the skin color (especially red, the a* value) depended on the radiation dose applied to the skin and that the objective spectrophotometric measurements correlated well with the subjective CTC scores [14]. They concluded that for classification of acute radiation toxicity there seems to be no need to replace the common CTC scoring with technically more sophisticated methods.…”
Section: Discussionmentioning
confidence: 99%
“…In most previous studies, the extent of erythema was determined with subjective means, such as visual inspection. Some attempts to establish objective measurements have been reported in the literature [4,11,12,14,21,22], i.e., visual reflectance spectroscopy and determination of a high-frequency dielectric constant [15]. These results have prompted the present study, which is concerned with the development of an objective assessment method for skin reaction that can be used by multiple observers, especially when a multi-institute trial is involved.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore conducted the present study to examine the radiation dermatitis following radiotherapy in patients who underwent NST and control group. In addition, as several objective assessments tools have been used because of their reliance and reproducibility in the areas of dermatology and other fi elds including radiology, [4][5][6][7][8][9] we included them in this study and examined radiation dermatitis by objective methods.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Based on clinical exam findings, physicians assigned a grade from 0 (absent) to 4 (severe). Skin toxicity is primarily evaluated by visual inspection based on changes in color (usually melanin), while subcutaneoustissue toxicity is primarily evaluated by palpation.…”
Section: Introductionmentioning
confidence: 99%